Muhammad Ali Pasha: Inovasi Pendidikan Islam - Harahap, Radinal Mukhtar (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ar-Raudlatul Hasanah, Medan, 2018)
History, although in basic understanding seems to talk about something that has passed,actually save a lot of lessons. This paper departs from a character's study of MuhammadAli Pasha who made many innovations in the field of Islamic education. He was found asa person who has a unique side, namely his personality who has no history of educationin childhood because of the pressure of life but grew as a leader who made manyinnovations. Some innovations that can be called are its policy of putting thegovernment as the center that develops education itself. Another innovation is theongoing traditional and modern educational activities together so that the scientificscope is separated from the dichotomous aspects. Muhammad Ali Pasha was also notedas a leader who paid attention to the development and expansion of the education areaso as to bring in European teachers to be able to take their expertise and practice in theEgyptian region, besides sending Egyptian youth to study in other regions to becomecadres in the realm he wanted to grow and develop. Even so, it does not mean thatMuhammad Ali Pasha's contribution and contribution in educational innovation can beswallowed up to be realized in Islamic educational institutions. More in-depthassessment of aspects, content and impacts that have been carried out to take what isneeded and leave what is not needed.